Asuhan Kebidanan Berkelanjutan/Continuity Of Care - Salsabila Putri Aprianti; Megawati Arpa; Fitri Wahyuningsih Nur; Sulfi Sulfi; Maharani Maharani (Journal on Education, 2023)
MMR and IMR are indicators to see health status and assess the level of ability to provide health services, which is still a major problem in developing countries. The purpose of writing this article is to provide Continuity Of Care midwifery care for pregnant, maternity, postpartum, BBL, and family planning women using standard midwifery care, so that the writer/reader is able to apply continuous midwifery care. Type of coc research This type of research is qualitative research. In this study, the experimental group will receive treatment, which is given care using the CoC method. In COC data types, we use 3 types of data collection, namely, primary data, secondary data and tertiary data. Objectively and subjectively which includes health records of postpartum mothers, newborns and records of the results of pregnancy and postpartum services data collection techniques. Data collection was carried out through interviews, document review and participatory observation. Data analysis comes from subjective data and objective data taken from providing care to Continuity Of Care participants starting from pregnancy, postpartum, newborn and family planning which will then be analyzed in accordance with Varney Midwifery Management and SOAP Documentation